A Rare Occurrence of Ambiguous Genitalia in Meckel-Gruber Syndrome (MGS): A Case Report - Bansal Sharad; Jangir Narendra; Sharma Rambabu (Mashhad University of Medical Sciences, 2019)
Background: Meckel-Gruber Syndrome (MGS) is a rare autosomal recessive congenital syndrome with triad of encephalocele, polydactyly, and polycystic kidneys. The worldwide incidence of the MGS is 1 in 1.3-1 in 140,000 live births. The highest incidence of 1 per 1,300 live births (carrier rate of 1 in 18) was reported in Gujarati Indians. MGS is caused by mutation in the meckelin transmembrane receptor (MKS3) located in the interior of the cells in the ciliary transition zone. Therefore, MGS as a fatal congenital syndrome belongs to a group of diseases known as ciliopathies. Most of the fetuses affected by this syndrome die before birth or soon after birth due to oligohydramnios, respiratory failure, and renal failure. There are few case reports of this syndrome associated with cleft lip and palate, inguinal hernia, congenital heart disease, micrognathia, microcephaly, and other abnormalities. Case report: We report a case of unusual and interesting occurrenceof ambiguous genitalia in the MGS syndrome. Conclusion: The MGS is a rare fatal syndrome and can be diagnosed prenatally. In the current case, we observed that ambiguous genitalia should be taken into consideration, in addition to the cardinal features. Parents should be counselled about the outcomes of a child, as well as the chance of recurrence (25%) in the subsequent pregnancies.